The Ability of Elementary School Students in Compiling Puzzles on the Pancasila Symbol Material - Ilmawati Fahmi Imron (STAI Hubbulwathan Duri, 2021)
The purpose of this study was to analyze the students' ability to construct a puzzle of Pancasila’ symbols by applying the STAD learning’s model to grade 1 students at SDN Gayam 3 Kediri. The method used in this research is descriptive qualitative. Data collection techniques are in the form of teacher and student observations, results of field notes, and documentation. Based on the research results with reference to the research instrument in the form of teacher observation data with a percentage of 73.6% then observation of student activity with a percentage of 64.2%, then based on the results of field notes and documentation it was stated that grade 1 students of SDN Gayam 3 Kediri were able to compile a puzzel Pancasila symbols with PPKn material even though there are still deficiencies. These shortcomings come from teachers, school infrastructure, and students themselves.